Modernism in Russian Piano Music Skriabin, Prokofiev, and Their Russian Contemporaries - Roberts, Peter Deane (Indiana University Press, 1993)
The purpose of this study is to review some of the techniques developed by Russian composers in the early part of the twentieth century, down to the active assertion of state control of the arts in the Soviet Union, which began in 1929. The study centers principally on music for the piano, with an emphasis on harmony and both tonal and nontonal structures.